Characteristics of Smart Packaging Film Labels from Senduduk Flower Extract (Melastoma malabathricum L.) Using Carriers from Paper, Chitosan and Starch - Sari, Dini Novita; Putri, Annisa; Yulianto, Kiki (JURNAL AGROINDUSTRI HALAL, 2026)
Smart packaging film labels are used as indicator labels to determine the freshness of a product by utilizing natural dyes. Senduduk flower extract contains anthocyanins that have the potential to be used as dyes for film labels because they are sensitive to pH changes. The type of carrier used to transport natural dyes affects the quality of the indicator film label. The purpose of this study was to determine the best type of carrier for smart packaging film labels that use senduduk flower extract as a color indicator. This study used three types of carriers (chitosan, paper, and starch). The test parameters included the label’s response to NaOH and NH3, water vapor transmission rate, thickness, tensile strength, elongation percentage, moisture content, and barrier properties. Senduduk flower extract has a deep red color with a pH value of 2. The response of the indicator film label to NaOH and NH3 vapor for the three types of carriers underwent color changes based on the RGB value on each film label. These color changes were analyzed from digital photos and then read using an application to produce the average RGB color, Whatman paper had the lowest thickness was 0.05 mm, moisture content the lowest in the starch film label was 16.52%, water vapor transmission rate was the lowest in the starch film label was 0.74 g/hour m², and barrier strength Whatman paper the best was 17.67 mm, the mechanical properties of the film label with the lowest tensile strength on the chitosan film label were 26.89 N/cm2 and elongation the lowest on Whatman paper was 0.71%. All three types of carriers had good stability during five days of storage at room temperature as observed visually.